Influence of Silage Additives on In Vitro Rumen Fermentation Pattern of Wheat Straw and Green Maize Silage - Belim, Saman Yusufkhan; H. H. Savsani; M. R. Chavda; M. D. Odedra; D. D. Garg; V.K. Karangiya; Y. G. Kansagara (Indian Journal of Animal Nutrition, 2023)
The current investigation was conducted to study various combinations of biological and chemical additives on in vitro rumen fermentation parameters of wheat straw and green maize silage. Different silages were prepared using green maize fodder and wheat straw in the proportion of 10:0 & 7:3 ratio in plastic jar of 3 kg capacity (3 replication in each) by adding common salt @ 0.5%, urea @1% and molasses @ 1.5% in each silages with seven different treatments viz. Control (only green maize), WS (green maize and wheat straw in 7:3 ratio), X (WS added with Xylanase), LP (WS added with L. plantarum), LF (WS added with L. fermentum), LPLF (WS added with both bacterial inoculants) and XLPLF (WS added with Xylanase and both bacterial inoculants). Xylanase, L. plantarum and L. fermentum were used @ 1500 IU/g, 1 x 106 cfu/g and 2 x 106 cfu/g, respectively. All silages were used for in vitro study after 45 days of ensiling. The result showed that significantly (p<0.05) higher TVFA content was noticed in Xylanase inoculated silage during in vitro rumen fermentation. Values of in vitro rumen ammonia nitrogen (NH3-N) and total nitrogen (Total N) were found significantly (p<0.01) higher in L. plantarum and combination of L. plantarum and L. fermentum inoculated silage. IVDMD was noticed significantly (p<0.05) higher in Xylanase inoculated silage. Also, IVOMD and total gas production were significantly (p<0.01) higher in Xylanase treated silage. Partitioning factor (PF) was observed significantly (p<0.01) lower in Xylanase inoculated silage. Thus, keeping in mind, advantage of Xylanase inoculated silage during rumen fermentation it is inferred that Xylanase can be used as additive when maize and wheat straw are principal fodder for silage production in the ratio of 7:3 for maximum nutrient utilisation.